Teachers' Opinions About Using Instructional Software - Kazu, Ibrahim Yasar; Yavuzalp, Nuh (Turkish Education Assoc, 2008)
This descriptive study examines instructional software's usage in Information Technology (IT) classes. In this context, levels of using instructional software and teacher's attitude towards instructional software are tried to be highlighted. The population of this research is 471 teachers of 17 primary schools with IT classes in Elazig and Malatya city centers. Ministry of National Education organizes in-service learning courses for teachers in order to teach how to run their IT classes effectively. This research points out that in these in-service courses, many teachers introduce the computer for the first time and this course helps the other teachers to use it more efficiently. Teachers signify that they can use computers for different aims as well. On the other hand, it is observed that many teachers fail to use instructional software in their lessons. It's understood that most teachers don't know if there is any software about their branches in their schools or not. Teachers think that if instructional software is used during lessons, learning the concepts of lesson topics will be easier; performance of the students and their success will be positively affected.
Keywords: Computer; instructional software; information technology